Deproteinization is Necessary for the Accurate Determination of Ammonia Levels by Glutamate Dehydrogenase Assay in Blood Plasma From Subjects With Liver Injury - Vodenicarovova, Melita; Skalska, Hana; Holecek, Milan (Laboratory medicine, 2017)
Abstract Objective To determine the effect of presence of high concentrations of nicotinamide adenine dinucleotide (NADH)– and nicotinamide adenine dinucleotide phosphate (NADPH)–consuming enzymes on the accuracy of glutamate dehydrogenase (GLDH) assay for ammonia. Methods We measured ammonia concentrations using GLDH and NADH or NADPH in blood-plasma specimens and specimens deproteinized by sulfosalicylic acid from CCl4-treated or control rats. The nonspecific oxidation of NADH and NADPH was measured in mixtures without GLDH. Results We observed a gradual decrease (~0.5%) in absorbance in the plasma of controls after the addition of NADH but not after adding NADPH. The decrease in absorbance in plasma of CCl4-treated animals was 13.2% and 5.2% after the addition of NADH and NADPH, respectively. The decrease in absorbance was not detected in deproteinized specimens. The values of ammonia concentration were higher in the plasma specimens compared with the deproteinized ones. Conclusion Deproteinization is necessary for accurate measurement of ammonia using GLDH assay in the blood plasma of subjects with liver injury.